The role of ESCRT proteins in attenuation of cell signalling. (20th January 2009) - Rodahl, Lina M.; Stuffers, Susanne; Lobert, Viola H.; Stenmark, Harald
Abstract : The ESCRT (endosomal sorting complex required for transport) machinery consists of four protein complexes that mediate sorting of ubiquitinated membrane proteins into the intraluminal vesicles of multivesicular endosomes, thereby targeting them for degradation in lysosomes. In the present paper, we review how ESCRT-mediated receptor down-regulation affects signalling downstream of Notch and growth factor receptors, and how ESCRTs may control cell proliferation, survival and cytoskeletal functions and contribute to tumour suppression.